Selection of optimal q RT-PCR reference genes for gene expression studies in foxtail millet - Li, Zhiyong; Zhu, Yanbin; Wang, Nan; Bai, Hui; Dong, Li; Quan, Jianzhang; Dong, Zhiping (The Indian Journal of Genetics and Plant Breeding, 2016)
Appropriate reference gene is very important for gene expression analysis by the quantitative RT-PCR (qRT-PCR), but no systematics research have been carried out in foxtail millet.In this study,the mRNA expression were investigated by qRT-PCR for six candidate reference genes, 25S rRNA, 18S rRNA, 17S rRNA, GAPDH, ACTB and UBQ under three different experimental conditions including different stages of leaf rust, five plant organs and seven different foxtail millet cultivars. The results obtained with GeNorm, NormFinder and BestKeeper software tools showed stable and uniform expression of 25S rRNA among different cultivars, 18S rRNA under the different conditions of leaf rust infection and 17S rRNA in different foxtail millet organs The list of reference genes confirmed in present study will be useful for genes expression analysis in foxtail millet under different conditions.